By-laws for natural resource management: Insights from Africa - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Africa's rural populations depend heavily on natural resources, which have been continuously deteriorating due to rapid population growth, increasing market pressures, high rates of poverty, and inappropriate natural resource management (NRM) policies of governments. The failure of top-down approaches to the regulation and administration of natural resources has increased attention on the role of decentralized administrative structures, user groups, and customary governance institutions.